Laccase removal of 2‐chlorophenol and sulfamethoxazole in municipal wastewater. (25th February 2019) - Haugland, J. Oliver; Kinney, Kerry A.; Johnson, William H.; Camino, Marina Montserrat Atilano; Whitman, Christian P.; Lawler, Desmond F.
Abstract: Laccases were studied for their ability to remove two compounds, 2‐chlorophenol and sulfamethoxazole, in batch studies, both in buffered solutions and in wastewater samples from different points in a municipal water resource recovery facility. Two enzymes with and without a mediator (acetosyringone) were investigated: a commercial product derived from Myceliphthora thermophile and a laboratory‐generated enzyme mix derived from Tramates versicolor . The chlorophenol was removed rapidly by the commercial enzyme in the presence of acetosyringone, but the primary products were coupling complexes of the reactants. Excellent removal was achieved without acetosyringone by the natural enzyme mix. Sulfamethoxazole was poorly removed in all laboratory‐generated chemically buffered solutions, but was very well removed, without the addition of mediators, in secondary effluent suspensions from a municipal water resource recovery facility. Mechanistic studies are still required, but the results suggest that treatment via direct addition of enzymes is feasible to remove recalcitrant compounds in municipal wastewater.